1996
DOI: 10.1073/pnas.93.18.9748
|View full text |Cite
|
Sign up to set email alerts
|

Matrilysin is expressed by lipid-laden macrophages at sites of potential rupture in atherosclerotic lesions and localizes to areas of versican deposition, a proteoglycan substrate for the enzyme.

Abstract: Matrilysin is expressed by lipid-laden macrophages at sites of potential rupture in atherosclerotic lesions and localizes to areas of versican deposition, a proteoglycan substrate for the enzyme ( ABSTRACTCertain matrix metalloproteinases (MMP) are expressed within the fibrous areas surrounding acellular lipid cores of atherosclerotic plaques, suggesting that these proteinases degrade matrix proteins within these areas and weaken the structural integrity of the lesion. We report that matrilysin and macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
240
4
11

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(274 citation statements)
references
References 39 publications
19
240
4
11
Order By: Relevance
“…Research indicates that these proteoglycans do influence cell behavior by blocking adhesion motifs from RGD-containing molecules and also binding TGF-b. 85 The last class of ECM proteins are glycoproteins. Glycoproteins are carbohydrates with distinct active domains and play key roles in cell signaling.…”
Section: Chemical Cues In Bonementioning
confidence: 99%
“…Research indicates that these proteoglycans do influence cell behavior by blocking adhesion motifs from RGD-containing molecules and also binding TGF-b. 85 The last class of ECM proteins are glycoproteins. Glycoproteins are carbohydrates with distinct active domains and play key roles in cell signaling.…”
Section: Chemical Cues In Bonementioning
confidence: 99%
“…However, full activation of proMMP-7 requires both a molar excess of MMP-3 and an extended incubation, suggesting MMP-3 is not an efficient activator of MMP-7 (Imai et al, 1995). Furthermore, MMP-3 is not typically co-expressed with MMP-1 (Parks, 1999;Saarialho-Kere et al, 1994) nor with MMP-7 in vivo (Dunsmore et al, 1998;Halpert et al, 1996;Rudolph-Owen et al, 1997). Second, if co-localized, the putative activating MMP may not be present in sufficient relative amounts to cleave the zymogen, particularly in a pericellular microenvironment that contain high concentrations of other or authentic substrates.…”
Section: Activation Of Prommps By Mmpsmentioning
confidence: 99%
“…Kinetic studies with model substrates have demonstrated that specific enzymes degrade some substrates more efficiently than others. For example, both MMP-2 and MMP-9 act on cleaved collagen better than other MMPs, (Mackay et al, 1990) and human MMP-7 is a more potent proteoglycanase and elastase than other MMPs (Filippov et al, 2003;Halpert et al, 1996). Thus, in a tissue environment, which contains many potential substrates, selectivity of MMP catalysis, in addition to being regulated by the concentration of active enzyme, may be directed by the concentration of a preferred substrate relative to that of other potential substrates within range of a secreted MMP.…”
Section: Compartmentalizationmentioning
confidence: 99%
“…For example, matrix metalloproteinase (MMP)-1 (Perides et al 1995), -2 (Passi et al 1999), -3 (Perides et al 1995, Halpert et al 1996), -7 (Halpert et al 1996, and -9 (Passi et al 1999) have been shown to degrade native, purified versican in vitro. Whereas MMP-8 cleaves aggrecan, the activity of this MMP against versican has not been studied.…”
Section: Proteinases Capable Of Cleaving Versicanmentioning
confidence: 99%